Health promotion model in the utilization of health services for Indonesian social security agency for health participants - Mustikawati, Irma F.; Sulaeman, Endang S.; Subiyanto , Achmad A.; Suminah, Suminah (Narra J, 2024)
Health promotion models are essential for enhancing community health and facilitating access to quality health services. Understanding the effects of these models on the utilization of health services among participants of the Indonesian Social Security Agency for Health (Badan Penyelenggara Jaminan Sosial Kesehatan/BPJS) provides valuable insights for developing effective health promotion strategies. The aim of this study was to assess the impact of health promotion on the utilization of health services among BPJS health participants, focusing on the mediating roles of perception, self-efficacy, expected results, and social support, using structural equation modeling (SEM). A descriptive, quantitative research design was employed, involving 160 BPJS health participants at Prof. Dr. Margono Soekarjo Hospital, Purwokerto, Indonesia. Data was collected using structured questionnaires, with participants selected through purposive sampling. SEM analysis, performed using AMOS software, was utilized to examine the relationships among health promotion, perception, self-efficacy, social support, expected outcomes, and health service utilization behavior. The SEM analysis revealed that health promotion significantly influenced health service utilization behavior directly (critical ratio (CR)=2.741; p=0.011). Furthermore, health promotion had a significant effect on perception through self-efficacy (CR=2.500; p=0.012).  Perception also significantly influenced behavior through self-efficacy (CR=3.789, p<0.001), while its indirect effect on behavior through outcome expectations was not significant (CR=0.908; p=0.958). Social support directly affected behavior (CR=2.267; p=0.023) and exerted both direct and indirect effects on behavior through self-efficacy (CR=3.789; p<0.001) and outcome expectations via self-efficacy (CR=6.267; p<0.001). However, self-efficacy did not significantly influence the behavior of utilizing BPJS health services through outcome expectations (CR=0.237; p=0.185). The findings indicate that health promotion significantly enhances the utilization of health services among BPJS health participants by improving perceptions and self-efficacy. Social support emerges as a critical factor in influencing health service utilization behavior and shaping outcome expectations through perception. In conclusion, future health promotion strategies should prioritize strengthening perceptions, enhancing self-efficacy, and leveraging social support to improve health service outcomes effectively.